VOCABULARY LEARNING STRATEGIES EMPLOYED BY ENGLISH DEPARTMENT STUDENTS OF STATE POLYTECHNIC OF BENGKALIS ACROSS DIFFERENT PROFICIENCY LEVELS. - Rionaldi Rionaldi; Boni Saputra (Universitas Negeri Padang, 2016)
This research was aimed at finding out vocabulary learning strategies employed by English Department students of State Polytechnic of Bengkalis across different proficiency levels. The subjects of the study were 28 students of English Department of Bengkalis State Polytechnic academic year 2014/2015. The questionnaire was used to collect the data, consisting of 32 items classified under three strategy categories; discovering meaning of new vocabulary (DMV), retaining knowledge of the newly-learned vocabulary (RKV), and Further Consolidation Vocabulary strategies (FCV). The quantitative data from questionnaire were analyzed using mean score. A Test of English for International Communication (TOEIC) was also administered to identify students' English language proficiency levels based on Puengpipattrakul (2007);Elementary (200-395), intermediate (400-595), working proficiency (600-795). The findings of this descriptive research revealed that the working proficiency level reported the highest frequency of overall strategy use, the intermediate level's frequency of use was slightly lower, and the elementary level had the lowest frequency of use. In DMV strategies, both working proficiency and intermediate levels used guessing strategy as the most frequently used strategy. In contrast, elementary level used dictionary-use strategy as the most frequently used DMV strategy. In RKV strategies, working proficiency level used association as the most frequently used strategy. In contrast, both elementary and intermediate level used repetition strategy as the most frequently used RKV strategy. In further consolidation vocabulary (FCV), all working proficiency, intermediate and elementary levels used expanding more frequently than practice strategy.